The analysis of cultural contents in the ELT textbook for senior high school students - Adelliya, Sabella Nisya; Andayani T, Made Adi; Fitriani, Ika (Journal of English Language Teaching and Learning (JETLE), 2025)
Integrating cultural content into English language learning is crucial, especially in Indonesia where English is taught as a foreign language. Cultural elements can be introduced through various educational settings, particularly via ELT textbooks used in schools. While previous studies have examined culture in textbooks aligned with the 2013 Curriculum, this study investigates the cultural categories represented in the ELT textbook Bahasa Inggris English for Change for eleventh-grade students. Using a content analysis approach, the study analyzed both visual and textual artifacts based on Cortazzi and Jin’s cultural categories: Source Culture, Target Culture, and International Culture. The results show that all three categories are present across 20 identified artifacts. Source Culture is the most frequently represented (11 artifacts), followed by International Culture (5 artifacts), while Target Culture appears the least (4 artifacts). The study recommends that teachers incorporate a more balanced range of cultural materials, that curriculum developers integrate source, target, and international cultural elements more systematically, and that policy support be strengthened to promote equitable cultural representation in national ELT materials.